2021
DOI: 10.1159/000515114
|View full text |Cite
|
Sign up to set email alerts
|

MiR-221-3p as a Potential Biomarker for Patients with Psoriasis and Its Role in Inflammatory Responses in Keratinocytes

Abstract: <b><i>Introduction:</i></b> This study investigated serum miR-221-3p levels in psoriatic patients and the characterization of serum miR-221-3p in keratinocyte inflammatory responses was further assessed. <b><i>Methods:</i></b> qRT-PCR was used to detect the expression level of miR-221-3p in the serum of 46 patients with psoriasis and 42 healthy controls. The receiver operating characteristic curve evaluated the diagnostic ability of miR-221-3p in psoriasis. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Of note, previously identified deregulated miRNAs in AD and PV lesional skin have been identified here as well: including miR-31, miR-21, miR-203, miR-146a, miR-24, miR-27, miR-193 and miR-221 25 , 26 (Supplementary Tables S1 and S2 ).…”
Section: Resultssupporting
confidence: 66%
“…Of note, previously identified deregulated miRNAs in AD and PV lesional skin have been identified here as well: including miR-31, miR-21, miR-203, miR-146a, miR-24, miR-27, miR-193 and miR-221 25 , 26 (Supplementary Tables S1 and S2 ).…”
Section: Resultssupporting
confidence: 66%
“…We used miRNet to identify hub genes-related key miRNAs that possibly participate in CDLE. The mir-221-3p, which is implied to be involved in both lupus nephritis and alopecia 28,29 , was found recently up-regulated in keratinocytes induced by UVB and was positively correlated with the expression levels of IL-17 30,31 .…”
Section: Discussionmentioning
confidence: 98%
“…microRNAs are non-coding small RNAs that can regulate and target various proteins, genes, and signaling pathways [ 3 , 4 ]. Owing to their stable expression and ease of detection, blood microRNAs have been widely used as biomarkers for the diagnosis and prognosis of many diseases [ 5 , 9 , 24 , 25 ]. In the study, plasma microRNA-221-3p levels were higher in the POCD group, and a subsequent binary regression analysis found that the postoperative plasma microRNA-221-3p level was an independent predictor of POCD.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies implicated a relationship between microR-221-3p and inflammation, microRNA-221-3p could mediate the antitumor effects of IFN-α [ 29 ], microRNA-221-3p and microRNA-92a-3p are reportedly associated with smoking-induced inflammation in COPD (chronic obstructive pulmonary disease) [ 30 ], microRNA-221-3p could drive the shift of macrophages towards pro-inflammatory functions by inhibiting the activation of JAK3/STAT3 [ 31 ]. Moreover, Meng et al found that plasma microRNA-221-3p was positively correlated with the expression levels of TNF-α, IL-17A, and IL-22 in patients with psoriasis [ 24 ]. Presently, there are several hypotheses about the pathogenesis of POCD, which are related to inflammation of the central nervous system, nerve cell apoptosis, dysfunction of the cholinergic nervous system, and oxidative stress injury.…”
Section: Discussionmentioning
confidence: 99%